1984
DOI: 10.1002/ajh.2830160303
|View full text |Cite
|
Sign up to set email alerts
|

Sideroblastic anemia: Differences in bone marrow erythroid colony (CFUe) growth responses to erythropoietin in plasma clot and methylcellulose cultures

Abstract: Bone marrow cells from three patients with idiopathic acquired sideroblastic anemia and one with X-linked sideroblastic anemia were simultaneously cultured in plasma clot and methylcellulose cultures in order to evaluate their erythroid colony (CFUE) cloning potential in these two systems. In contrast to normals, sideroblastic anemia bone marrow cells demonstrated a marked ability to form erythropoietin (Epo)-independent CFUE in methylcellulose culture, and were inhibited in their ability to generate CFUE in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Moreover, no endogenous CFU-E or BFU-E growths (without EPO) were obtained, in contrast to the extremely abundant endogenous CFU-E reported by Lutton et al [10] in X-linked SA.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Moreover, no endogenous CFU-E or BFU-E growths (without EPO) were obtained, in contrast to the extremely abundant endogenous CFU-E reported by Lutton et al [10] in X-linked SA.…”
Section: Discussioncontrasting
confidence: 71%
“…To date, there are very few reports on the functional and morphological characteristics of colonies grown in vitro from erythroid burst forming units (BFU-E) or from colony forming units (CFU-E) from patients with SA [8,10,12]. In addition most of them concerned adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the erythroblastic island niche is a fundamental feature of in vivo erythropoiesis, this process can be replicated ex vivo . The cells are able to differentiate in cultured clot (Lutton et al ., ), semi‐solid (Metcalf, ) or liquid (Gartner and Kaplan, ) media. Fibach et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although the erythroblastic island niche is a fundamental feature of in vivo erythropoiesis, this process can be replicated ex vivo. The cells are able to differentiate in cultured clot (Lutton et al, 1984), semi-solid (Metcalf, 1981) or liquid (Gartner and Kaplan, 1980) media. Fibach et al (1989) further advanced the use of liquid suspension cultures of erythroblasts using primary human haematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that SA bone marrow and peripheral blood mononuclear cells yield a marked reduction in erythroid colony growth when cultured in plasma clot culture with erythropoietin (Epo) [20,21]. In other experiments, we found that there is a considerable difference in SA bone marrow CFU-e growth in the absence or presence of Epo, depending on the type of culture method used [22]. In this respect, SA marrows demonstrated a marked ability to form Epo-dependent and Epo-independent CFU-e in methylcellulose cultures, but failed to do so in plasma-containing cultures.…”
Section: Introductionmentioning
confidence: 56%